Derivation of Newton's Forward Difference Interpolation Formula
Newton's Forward Difference Interpolation Formula:
Let y = f(x) be a function of x and let us suppose that yᵢ = f(xᵢ) ...(1) for i = 1,2,3,.....,n satisfying the condition xᵢ = x₀+ih where
'h' is the interval of difference .
Now our aim is to constuct a function Φ(x) of degree not higher than n such that
Φ(xᵢ) = yᵢ ............(2)
Since Φ(x) is a polynomial of degree n
then we can write
Φ(x) = a₀ + a₁(x-x₀) + a₂(x-x₀)(x-x₁) + a₃(x-x₀)(x-x₁)(x-x₂)+......
+ aₙ(x-x₀)(x-x₁)(x-x₂).....(x-xₙ₋₁)...(3)
Let us find the value of a₀,a₁,a₂.....aₙ satisfying the equations (2) and (3)
From equation (2) , we get Φ(x₀) = y₀
From equation (3) , we get Φ(x₀) = a₀
so , a₀ = y₀ ...........(4)
From equation (2) we get Φ(x₁) = y₁
From equation (3) we get Φ(x₁) = a₀+a₁(x₁-x₀)
Therefore y₁ = a₀ + a₁(x₁-x₀)
⇒y₁ = y₀ + a₁h as a₀=y₀ and h = x₁-x₀
⇒a₁ = y₁-y₀ / h
⇒ a₁ = Δy₀ / h .........(5)
From equation (2) we get Φ(x₂) = y₂ and from equation (3) we get
Φ(x₂) = a₀ + a₁(x₂-x₀)+a₂(x₂-x₀)(x₂-x₁)
Therefore
y₂ = a₀ + a₁(x₂-x₀) + a₂(x₂-x₀)(x₂-x₁)s
Φ(xᵢ) = yᵢ ............(2)
Since Φ(x) is a polynomial of degree n
then we can write
Φ(x) = a₀ + a₁(x-x₀) + a₂(x-x₀)(x-x₁) + a₃(x-x₀)(x-x₁)(x-x₂)+......
+ aₙ(x-x₀)(x-x₁)(x-x₂).....(x-xₙ₋₁)...(3)
Let us find the value of a₀,a₁,a₂.....aₙ satisfying the equations (2) and (3)
From equation (2) , we get Φ(x₀) = y₀
From equation (3) , we get Φ(x₀) = a₀
so , a₀ = y₀ ...........(4)
From equation (2) we get Φ(x₁) = y₁
From equation (3) we get Φ(x₁) = a₀+a₁(x₁-x₀)
Therefore y₁ = a₀ + a₁(x₁-x₀)
⇒y₁ = y₀ + a₁h as a₀=y₀ and h = x₁-x₀
⇒a₁ = y₁-y₀ / h
⇒ a₁ = Δy₀ / h .........(5)
From equation (2) we get Φ(x₂) = y₂ and from equation (3) we get
Φ(x₂) = a₀ + a₁(x₂-x₀)+a₂(x₂-x₀)(x₂-x₁)
Therefore
y₂ = a₀ + a₁(x₂-x₀) + a₂(x₂-x₀)(x₂-x₁)s
⇒y₂ = y₀ + (y₁-y₀)(2h)/h + a₂(2h)(h)
⇒ y₂ = y₀ + 2(y₁-y₀) + a₂(2h²)
⇒ a₂ = y₂-2y₁+y₀ / 2!h²
⇒ a₂ = Δ² y₀/2!h² ..........(4)
From equation (2) we get Φ(x₃) = y₃
From equation (3) we get
Φ(x₃) = a₀ + a₁(x₃-x₀) + a₂(x₃-x₀)(x₃-x₁)
+ a₃(x₃-x₀)(x₃-x₁)(x₃-x₂)
⇒y₃ =y₀+(y₁-y₀)(3h)/h+
(y₂-2y₁+y₀)(3h)(2h)/2
+ a₃(3h)(2h)(h)
⇒ y₃ = y₀ + 3(y₁-y₀) + 3y₂-6y₁ + 3y₀ + 6a₃h³
⇒ a₃ = y₃ + 3y₁ -3y₂-y₀ /6h³ = Δ³y₀ /1*2*3*h³
= Δ³y₀/3!h³
Therefore a₃ = Δ³y₀ /3!h³ ...............(7)
Continuing in the process ,we get
a₄ = Δ⁴y₀/4!h⁴ , a₅ = Δ⁵ y₀ /5! h⁵ ,........
aₙ = Δⁿy₀ / n!hⁿ ............(8)
Now , substituting the values of a₀, a₁,a₂...aₙ
in equation (3) ,we get
Φ(x) = y₀ + Δy₀(x-x₀)/h + Δ²y₀(x-x₀)(x-x₁)/2!h²
+ Δ³ y₀ (x-x₀)(x-x₁)(x-x₂)/3!h³ + ......
+ Δⁿy₀(x-x₀)(x-x₁)......(x-xₙ₋₁)/n!hⁿ ....(9)
The equation (9) is known as Newton's Forward Difference Interpolation
Formula .
But for practical purpose this formula is modified by using the equation
x = x₀ + sh ..........(10)
Then we have x - x₀ = sh , so s = x - x₀ / h
x-x₁ = x₀+sh - (x₀+h) = (s-1)h
x-x₂ = x₀+sh - (x₀+2h) = (s-2)h
x-x₃ = x₀+sh - (x₀ +3h) = (s-3)h
..............................................................
..............................................................
x- xₙ₋₁ = x₀ +sh - {x₀+ (n-1)h} = [s-(n-1)]h
...........(11)
Substituting these values of (x-x₀),(x-x₁),
(x-x₂),.......(x-xₙ) in equation (9) , we get
Φ(x) = Φ(x₀+sh)
= y₀ + sΔy₀ + s(s-1)Δ²y₀ /2!
+ s(s-1)(s-2)Δ³y₀/3! + .........
+ s(s-1)(s-2).....{s-(n-1)}Δⁿy₀/n! ......(12)
This equation (12) is the Modified Newton's Forward Difference Interpolation Formula.
For Example :
Evaluate f(1.2) using the following table .
x 0 1 2 3 4
f(x) 1 1.5 2.2 3.1 4.2
Solution :
The finite difference table is
x f(x) Δf(x) Δ²f(x)
0 1
0.5
1 1.5 0.2
0.7
2 2.2 0.2
0.9
3 3.1 0.2
1.1
4 4.2
Here x = 1.2 ,let x₀ = 1.0
Then s = x - x₀ /h = 1.2-1 / 1 = 0.2
Now by Newton's Forward Difference Interpolation Formula , we get
y(x) = y₀ + sΔy₀ + s(s-1) Δ²y₀ / 2!
Therefore
y(0.2) = 1.5 + 0.2 * 0.7 + 0.2(0.2-1) *0.2 /2
= 1.624
which is required solution .
for more
2 2.2 0.2
0.9
3 3.1 0.2
1.1
4 4.2
Here x = 1.2 ,let x₀ = 1.0
Then s = x - x₀ /h = 1.2-1 / 1 = 0.2
Now by Newton's Forward Difference Interpolation Formula , we get
y(x) = y₀ + sΔy₀ + s(s-1) Δ²y₀ / 2!
Therefore
y(0.2) = 1.5 + 0.2 * 0.7 + 0.2(0.2-1) *0.2 /2
= 1.624
which is required solution .
for more
Comments
Post a Comment
If Any Doubt Ask Me